Becoming an Antiracist Neonatal Community. (February 2021) - Vance, Ashlee J.; Bell, Tracey
Abstract : Background: There are pervasive and documented disparities in maternal and infant outcomes related to race and ethnicity. Critical awareness is growing in our current cultural environment about strategies to improve health equity, the need to challenge implicit bias, and dismantle racism in healthcare to decrease racial health inequities. Methods: In this article, we provide a summary of health inequities that exist within the perinatal/neonatal population and offer strategies for initiating conversations and improving health equity by challenging bias and increasing diversity. Results: Transformative leaders must understand the evidence related to health disparities, understand social drivers of inequity issues, and identify solutions to influence change. Implications for Practice: With heightened awareness and examination of implicit bias, we can improve care for all infants and their families. Implications for Research: We need to continue research and quality improvement efforts to improve health equity. Furthermore, research is needed that focus on social determinants of health as drivers of preterm delivery and birth complications, rather than biological (eg, racialized) factors. Video Abstract available at: https://journals.lww.com/advancesinneonatalcare/Pages/videogallery.aspx?autoPlay=false&videoId=42